KEBIJAKAN KRIMINALISASI TERHADAP LARANGAN PADA MINUMAN BERALKOHOL DI KOTA JAMBI - Ruslan Abdul Gani (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Alcoholic beverages cause a variety of effects both on health and social ills in society. Therefore, the government issued a criminal policies for anyone producing, selling, consuming alcoholic beverages. One of the criminalization policy is made law No. 3 of 2008 on the Prohibition and Sale of Alcoholic beverages. policy, which is done through legislation and official bodies, which aims to establish a central norms of society. The results of the study obtained a conclusion that alcoholic beverages can result in danger to the wearer in addition, it also can lead to diseases such people, fights, sexual, abuse. Constraints in the statutory law enforcement investigators perceived problems while still less effort to overcome the habit of alcoholic beverages can be done in two ways: medically, and through psychological therapy.Keyword: policy, criminalization, alcoholic beverages